Label-free concurrent 5-modal microscopy (Co5M) resolves unknown spatio-temporal processes in wound healing - Markus Seeger (Nature Portfolio, 2021)
Seeger et al. demonstrate concurrent 5-modal microscopy (Co5M), combining optoacoustic, two-photon, second and third harmonic generation, and brightfield microscopy in one system. Longitudinal changes associated with the wound healing process in mouse ears were monitored label-free in vivo using complementary information obtained from the Co5M system to characterize wound shape, microvascular and collagen density, vessel size and fractality, and the plasticity of sebaceous glands.